PATIENT CHARACTERISTICS AND THE CAUSES OF LOW VISION AT PAJAJARAN SLB - Firdha Malisa Fauzia; Ine Renata Musa; Harry Emile Saroinsong (PAIFORI, 2022)
Low vision is a visual condition that requires careful monitoring. Rehabilitation problems have been caused by our society's lack of education and information. Many people still mistakenly believe that having low vision is the same as being blind. The study used a descriptive methodology and data from Cicendo Hospital's medical records. The information includes patient features and low vision causes. With an average age range of 7 to 24 years, SLB Pajajaran has a 57.8% prevalence of poor vision. Most people are consanguineous and lack family history. Anomalies in the cornea and retina are the primary culprits. A limited percentage of SLB Pajajaran's population still maintains functional eyesight, and those who do can still see well enough to perform simple tasks.